Adaptabilidad y producción de cuatro variedades de fréjol andino (Phaseolus vulgaris l.), en el cantón La Maná, 2014 - Guevara Moreno, Darwin Luis (2014)
The problem of the zone in the production of a single variety of beans promoted this study about the adaptability with other Andean varieties. This research was conducted in La Maná Canton, in the Professional Drivers' Union Residential Area, located to 4 km from the road to Manguila town for 72 days. The objectives of this research were to evaluate the adaptability and production of four varieties of Andean beans and compare against a control treatment, as well as to realize an economic analysis of the treatments. The design used was the Completely Randomized Block (CRB)….